Royalties do petróleo e sustentabilidade : análise jurídico-institucional em Sergipe - Aragão, Fábio Lima (2012)
The funds received as a result of oil royalties are a source of important and potentially transformative for states and municipalities located in areas of petroleum extraction. The dissertation work is meant to examine the application of royalties derived from activities related to the oil industry earned by states and municipalities. To achieve this purpose, there is analysis of the oil law, the administrative constraints that are submitted to public resources and the possibilities that public policy provides. It took into account the finiteness of the mines and oil fields, so the research aims to determine how these resources are potentially able to promote improvements in education, health, employment and income of the local population, focusing on sustainable social development for these municipalities . Assigning responsibilities for public managers in the application and investment is through public policy. The study sees the possibilities of better utilization of those resources through the creation of sovereign wealth funds and legal relationship of oil royalties.